2010
DOI: 10.1111/j.1558-5646.2010.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Mom in Charge? Implications of Resource Provisioning on the Evolution of the Placenta

Abstract: The Trexler-DeAngelis model shows that placentas are most likely to evolve in environments with consistent, high levels of resource availability. An assumption imperative to the model is that placental species abort embryos in low food conditions. They also lend support to hypotheses that suggest parent-offspring conflict in utero drives the evolution of the placenta. K E Y W O R D S :Life-history evolution, matrotrophy, parent-offspring conflict, poeciliopsis, resource partitioning, Trexler-Deangelis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 40 publications
(91 reference statements)
3
53
0
Order By: Relevance
“…Similarly, early broods are more likely to occur too early to allow for full and normal development, and an early brood could set the stage for a longer interval till the next birth. It has been suggested that abortions occur in poeciliids under normal conditions (Reznick et al, 1996) as a fitness strategy to eliminate offspring with low chances of survival (Banet et al, 2010;Trexler and DeAngelis, 2003). This is consistent with our hypothesized link between the abortions and toxic effects in the embryo.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, early broods are more likely to occur too early to allow for full and normal development, and an early brood could set the stage for a longer interval till the next birth. It has been suggested that abortions occur in poeciliids under normal conditions (Reznick et al, 1996) as a fitness strategy to eliminate offspring with low chances of survival (Banet et al, 2010;Trexler and DeAngelis, 2003). This is consistent with our hypothesized link between the abortions and toxic effects in the embryo.…”
Section: Discussionsupporting
confidence: 90%
“…Although matrotrophy relies on maternal mechanisms to transport nutrients from maternal blood to offspring across several cell layers (Biazik et al 2009;Moore 2012;Griffith et al 2013a), these mechanisms could be induced by embryonic cues to maternal tissues via embryonic hormones. Notably, the Trexler-DeAngelis and parent-offspring-conflict hypotheses are not mutually exclusive (Banet et al 2010). Parent-offspring conflict may be the mechanism that drives the evolution of matrotrophy, but matrotrophy may only be a viable strategy in environments where food abundance is consistently high during gestation or in species capable of aborting, reabsorbing, or cannibalizing poor-quality offspring when food is scarce.…”
Section: Introductionmentioning
confidence: 97%
“…If food resources are too limited to allow successful development of all embryos in a litter, Trexler and DeAngelis (2003) predicted that females should selectively abort, reabsorb, and/or cannibalize poor-quality embryos and reallocate their nutrients to other offspring in the litter. The Trexler and DeAngelis (2003) model has been tested several times in fish, in which food limitation during gestation causes reductions in matrotrophic provisioning, offspring size, and maternal mass in matrotrophic species but affects only maternal mass in lecithotrophic species (Marsh-Matthews and Deaton 2006;Banet et al 2010;Pollux and Reznick 2011;Riesch et al 2013). Food restriction rarely causes abortion or cannibalism of offspring in either matrotrophic or lecithotrophic fish (Banet and Reznick 2008;Banet et al 2010;Pollux and Reznick 2011; but see Riesch et al 2013).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations